Application of commingled thermoplastic composites on an airline seat backrest - Mattheyse, Richard (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.